The Influence of Financial Ratio and Corporate Governance on Financial Distress in Indonesian Islamic Banking Period 2013 – 2019 - Rizki Syaepullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aimed to analyze the factors that affect the financial distress in the Islamic Bank in Indonesia. The scope of this research is focused on the financial ratio variables that is operational cost and operating income, capital adequacy ratio and current ratio, and also focused on the corporate governance variables such as the board of commissioners and the board of directors. The sample was selected by purposive sampling method as many as 14 Islamic bank companies listed on the Indonesian Stock Exchange, which use the data collected within period 2013 – 2019. The data used is secondary data. The analyzing data using the fixed estimation model and classic assumption test. The results of this research showed that the financial ratio variables and corporate governance variables simultaneously affect financial distress conditions. The conclusion is the Board of Directors has no significant positive effect on financial distress conditions, but the Capital Adequacy Ratio and Current Ratio have a significant positive effect on financial distress conditions. While inversely proportional with the Operational Costs and Operational Income and the Board of Commissioners have a significant negative effect on financial distress. Penelitian ini bertujuan untuk menganalisis pengaruh financial ratio variables yaitu biaya operasional pendapatan operasional, capital adequacy ratio dan current rasio serta difokuskan pada corporate governance yang terdiri dari dewan komisaris dan dewan direksi yang mempengaruhi financial distress pada perbankan syariah. Sampel dipilih dengan purposive sampling method sebanyak 14 perbankan syariah yang terdaftar di Bursa Efek Indonesia dengan jangka waktu data pengambilan data selama 2013 – 2019. Data yang digunakan adalah secondary data. Analysis data menggunakan fixed effect model estimation dan classic assumption test. Hasil penelitian menunjukkan bahwa financial ratio variable dan corporate governance secara simultan berpengaruh terhadap kondisi financial distress. Penelitian ini menyimpulkan bahwa dewan direksi tidak berpengaruh secara signifikan secara positif terhadap kondisi financial distress, tetapi capital adequacy ratio dan current ratio berpengaruh secara signifikan secara positif terhadap kondisi financial distress. Sedangkan biaya operasional pendapatan operasional dan dewan komisaris yang berpengaruh signifikan secara negatif terhadap kondisi financial distress.